2023
DOI: 10.3390/nu15143112
|View full text |Cite
|
Sign up to set email alerts
|

IgE Mediated Shellfish Allergy in Children—A Review

Abstract: Shellfish is a leading cause of food allergy and anaphylaxis worldwide. Recent advances in molecular characterization have led to a better understanding of the allergen profile. High sequence homology between shellfish species and between shellfish and house dust mites leads to a high serological cross-reactivity, which does not accurately correlate with clinical cross-reactions. Clinical manifestations are immediate and the predominance of perioral symptoms is a typical feature of shellfish allergy. Diagnosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 156 publications
(198 reference statements)
0
1
0
Order By: Relevance
“…Our study showed the highest Pen m 1-sIgE rates (1.86%) and levels (9.98 kU A /L) out of all five evaluated shrimp molecules. Shellfish allergy often develops in late childhood or during adolescence [27]. In our study, the rates of sIgE in Pen m 1 and Pen m 2 showed a significant increase between the age groups of 1-5 and 5-13 years, and all evaluated shrimp molecules showed the highest sIgE rates in the age group of 13-18-year-olds.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Our study showed the highest Pen m 1-sIgE rates (1.86%) and levels (9.98 kU A /L) out of all five evaluated shrimp molecules. Shellfish allergy often develops in late childhood or during adolescence [27]. In our study, the rates of sIgE in Pen m 1 and Pen m 2 showed a significant increase between the age groups of 1-5 and 5-13 years, and all evaluated shrimp molecules showed the highest sIgE rates in the age group of 13-18-year-olds.…”
Section: Discussionsupporting
confidence: 51%
“…Protein profiles in shrimp with hypersensitivity may differ depending on the population, which is likely due to differences in genetics, environmental exposure, and dietary preferences. Therefore, it is important to determine the molecular profile for individual populations to ensure an optimal protein profile in shrimp allergy diagnostic tests [7,24,26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Fish and shellfish are common causes of food allergies worldwide, with higher prevalence found in Asian and Northern European countries where seafood is more frequently consumed. Ages of onset for fish and shellfish allergy are approximately 1 ½ years and 5 years, respectively, with a wide range reported for rates of resolution (Table 1 ) [ 21 , 60 , 61 ]. Sesame is an emerging culprit for food allergy in childhood, with estimated prevalence in children of 0.2–0.8% [ 25 , 62 , 63 ].…”
Section: Infancy and Early Childhoodmentioning
confidence: 99%